Corrosion Resistance of Hard Coat Anodized AA 6061 in Citric–Sulfuric Solutions - Cabral Miramontes, José Ángel; Gaona Tiburcio, Citlalli; Estupiñan López, Francisco Humberto; Lara Banda, María del Refugio; Zambrano Robledo, Patricia del Carmen; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Almeraya Calderón, Facundo; Chacón Nava, José G. (Molecular Diversity Preservation International, 2020)
Aluminum is a material widely used in aeronautical and transport industries due to its excellent mechanical and corrosion resistance properties. Unfortunately, aluminum alloys are susceptible to corrosion, which limits their use in some corrosive environments. The aim of this work is to characterize hard coat film fabricated by anodizing in a citric–sulfuric acid system using electrochemical techniques. The anodization process was carried out using an aluminum alloy AA 6061 anodization bath: a mix of citric and sulfuric acid solutions were used. For the anodizing process, two current densities were used, 1 and 7.2 A·cm−2. Anodized specimens obtained under different conditions were exposed to a 3.5 wt.% NaCl solution, and their electrochemical behavior was studied by electrochemical impedance spectroscopy (EIS) and cyclic potentiodynamic polarization (CPP) according to ASTM G106-15 and ASTM G5-13, respectively. Scanning electron microscopy (SEM) was employed to determinate the morphology and thickness of coatings. The results showed improved corrosion resistance in 6061 aluminum anodized in citric–sulfuric acid electrolyte compared to those anodized in sulfuric acid solution.